2020
DOI: 10.3390/app10020593
|View full text |Cite
|
Sign up to set email alerts
|

Geopolymer-Bonded Laminated Veneer Lumber as Environmentally Friendly and Formaldehyde-Free Product: Effect of Various Additives on Geopolymer Binder Features

Abstract: Environmentally friendly and formaldehyde-free laminated veneer lumber (LVL) was manufactured using geopolymer constituents as binder. The main aim of the study was to improve the bonding quality between the geopolymer binder and the wood constituents. To this end, the effect of various additives (phenol flakes, conventional silica fume, and grafted silica fume with 3-aminopropyltriethoxysilane (APTES)) in the geopolymer binder features were explored via gel time and viscosity measurements, differential scanni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…Previous studies also confirmed that a higher press temperature has a positive influence on the shear strength and bonding quality of the geopolymer binder [12,13]. This can be attributed to the higher dissolution of binder ingredients and the successful geopolymer network formation [24]. Notably, the shear strength of the geopolymer-bonded plywood was negatively influenced by further increasing the press temperature from 140 °C to 160 °C.…”
Section: Hot-pressing Tempearturementioning
confidence: 60%
See 4 more Smart Citations
“…Previous studies also confirmed that a higher press temperature has a positive influence on the shear strength and bonding quality of the geopolymer binder [12,13]. This can be attributed to the higher dissolution of binder ingredients and the successful geopolymer network formation [24]. Notably, the shear strength of the geopolymer-bonded plywood was negatively influenced by further increasing the press temperature from 140 °C to 160 °C.…”
Section: Hot-pressing Tempearturementioning
confidence: 60%
“…Finally, a steady increase of WA was observed after 384 h of water soaking. The increasing trend of regimes 2 and 3 are possibly due to the additional micro-cracks created in the hardened geopolymer when it was immersed in water [11,24]. As mentioned earlier, water may also cause cracking in geopolymer due to capillary forces.…”
Section: Lay-up Timementioning
confidence: 83%
See 3 more Smart Citations